1995
DOI: 10.2337/diab.44.6.614
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Linkage of Thymic T-Cell Proliferative Unresponsiveness to Mouse Chromosome 11 in NOD Mice: A Possible Role for Chemokine Genes

Abstract: Thymic and peripheral T-cells from NOD mice display a proliferative unresponsiveness on stimulation through the T-cell receptor/CD3 complex. Interleukin 4 reverses NOD T-cell unresponsiveness in vitro and prevents the onset of diabetes in vivo, suggesting a causal relationship between the T-cell unresponsiveness and diabetes susceptibility in NOD mice. Both quantitative trait loci analysis of BXD recombinant inbred mice and linkage analysis of NOD outcross populations reveal that the control of NOD thymic T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…It was reported that NOD mice have a defect in the TCR signaling cascade mediated through the protein kinase C/Ras/MAPK pathway (16)(17)(18). This NOD-specific trait, manifested by T cell hyporesponsiveness with reduced IL-2 and -4 secretion, was genetically mapped to gene(s) in the Idd4.2 region on chromosome 11 (39,40). The fact that the B6 allele of the Ctex/Cd3z region only partially restored the B6 IL-2 and IFN-g cytokine expression pattern and proliferation profile is compatible with a complementary function of the Idd4 and Ctex/Cd3z genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that NOD mice have a defect in the TCR signaling cascade mediated through the protein kinase C/Ras/MAPK pathway (16)(17)(18). This NOD-specific trait, manifested by T cell hyporesponsiveness with reduced IL-2 and -4 secretion, was genetically mapped to gene(s) in the Idd4.2 region on chromosome 11 (39,40). The fact that the B6 allele of the Ctex/Cd3z region only partially restored the B6 IL-2 and IFN-g cytokine expression pattern and proliferation profile is compatible with a complementary function of the Idd4 and Ctex/Cd3z genes.…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentrations were measured using a Nanodrop spectrophotometer, and cDNA was prepared from 300 ng total RNA using the Reverse Transcription Reagents (TaqMan, Applied Biosystems, Foster City, CA), according to the manufacturer's instructions. The following primers and probes were used to measure RNA expression: for the full-length CTLA-4, forward primer: 59-GGACGCAGATTTATGTCATTGATC- 39 Expression of the genes coding for 36B4 and b-actin was used as endogenous control. CTLA-4, 36B4, and b-actin primers and probes were designed using Primer Express (Applied Biosystems).…”
Section: Reverse Transcription Followed By Quantitative Pcrmentioning
confidence: 99%
“…On Chr 11, Tucker has identified D11Mit207 (29 cm) as a weak marker associated with serum gp70 [24]. Using BXD RI lines of mice, T-cell proliferative unresponsiveness in NOD mice was mapped to a region on Chr 11 (49 cm) [25]. These results suggest that both Chrs 7 and 11 contain genetic loci that predisposes to autoimmune disease and dysregulation of BM stem cell development [26].…”
Section: Quantitative Trait Loci (Qtls) Affecting the Haematopoietic mentioning
confidence: 99%
“…Mononuclear cell infiltration of pancreatic islets and the progressive Th1 cell-mediated destruction of insulin-producing ␤ cells herald the onset of autoimmune type I diabetes. Previously, we found that the genetic control of NOD T cell proliferative hyporesponsiveness to engagement of the TCR is linked to a central region on chromosome 11 that includes the CC chemokine gene family and the Idd4 diabetes susceptibility locus (15). We also found that IL-4 treatment and CD28 costimulation prevent Th1-mediated destructive insulitis and type I diabetes in NOD mice by potentiation of regulatory Th2 cell function (16 -18).…”
mentioning
confidence: 89%